Development of a novel, quantitative assay for determining the rate of activity of antimalarial drugs - Khan, Tasmiyah (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2013)
Malaria, caused by an intracellular Plasmodium parasite, remains a devastating disease, having claimed approximately 655 000 lives worldwide in 2010. The Medicines for Malaria Venture suggests a "single-dose radical cure" as the ideal malaria treatment since rapid clearance of blood-stage parasites and symptom relief improves patient compliance and limits drug resistance. Thus, novel antimalarials should be rapid-acting and assessing their rate of activity is critical to drug discovery. Traditional evaluation of this rate by morphological assessments is flawed by highly subjective, operator-specific interpretations, mainly due to heterogeneous parasite morphology under routine culture conditions. This study aimed to develop an alternative, quantitative assay. Energy is vital for the growth and maintenance of all living organisms. Commercially available kits allow rapid quantification of the cell's energy currency, ATP. Therefore, quantification of parasite ATP shows potential for diagnosing abnormal parasite metabolism and the kinetics of drug action. In this study, a rapid protocol for detecting ATP in Plasmodium falciparum parasites using a luminescence-based kit was developed and optimised. Furthermore, luciferase-expressing transgenic parasites, in which luciferase activity is detected using a similar kit, were acquired. The utility of both methods for evaluating the rate of drug-induced stress was explored using antimalarials with varying modes of action and, presumably, rates of activity. Results showed that parasite ATP remained unchanged, increased or decreased during drug exposure. Morphological examinations by light microscopy and a Recovery assay, aided interpretation of the drug-induced changes in parasite ATP. These investigations suggested that unchanged parasite ATP levels reflect poor drug action, increased ATP levels indicate a stress response and partially compromised viability, while significantly reduced ATP reflects severely compromised viability. Concerning the Luciferase assay, parasite luciferase activity decreased during drug exposure, even in the presence of proteasome inhibitors. Changes in parasite ATP and luciferase activity occurred at rates which suggested that chloroquine is slow-acting, mefloquine has a moderate rate of activity and artemisinin is rapid-acting. These findings are compatible with the expected rates of activity of these established antimalarials. Hence, measurement of parasite ATP and/or luciferase activity may support assessments of parasite health and the kinetics of antimalarial action during drug discovery
Keywords: Assay; ATP; Antimalarials -- Therapeutic use Malaria Malaria -- Drug therapy Adenosine triphosphate Luciferases Plasmodium falciparum